Peningkatan kapasitas peternak ruminansia melalui penyuluhan dan pelatihan fermentasi pakan di desa payung mulya, kecamatan pubian, kabupaten lampung tengah [Capacity building of ruminant farmers through counseling and training on feed fermentation in Payung Mulya Village, Pubian Sub-District, Central Lampung District] - Widiastuti, Lusia Komala; Sirat, Muhammad Mirandy Pratama; Setio, Slamet; Tantalo, Syahrio (The Institute for Research and Community Services (LPPM) Universitas Syiah Kuala (USK), 2025)
Increasing the capacity of farmers is one of the efforts made to improve livestock businesses, as it enables the productivity of the livestock raised to be more optimal. Therefore, the community service team of the Faculty of Agriculture, University of Lampung through the Klinik Pertanian Keliling Program routinely organizes extension and training-based activities to overcome problems in the livestock sector. This program aims to increase the capacity of ruminant farmers in Payung Mulya Village, Pubian Sub-District, Central Lampung District through integrated counseling on livestock maintenance, reproduction, and health management, as well as feed fermentation practices that include silage production from elephant grass and bran, and ammoniation of rice straw using urea. The evaluation of the activity was conducted by administering the same questionnaire both before (pre-test) and after (post-test) the program, which consisted of 29 questions related to livestock management, health, reproduction, and feed fermentation technology. A total of 40 participants took part in the activity, comprising 33 ruminant farmers from Payung Mulya Village and 7 students from the Community Service Program (KKN) of Universitas Lampung. The results of the community service activity demonstrated an increase in knowledge and skills, with improvements of 44.19% in livestock management (from 41.72% to 85.91%), 18.68% in livestock health (from 67.89% to 86.57%), 32.66% in livestock reproduction (from 55.41% to 88.07%), and 70.09% in feed fermentation technology (from 20.14% to 90.23%). This community service program concludes that it effectively enhanced the participants' knowledge and skills in livestock management, health, reproduction, and feed fermentation technology.